Actividades lúdicas interculturales y el ámbito de Relaciones Lógico-Matemáticas de los estudiantes de la Unidad Educativa “Manuel Rodríguez Orozco”, Ilapo-Guano. - Galarza Duchi, Nancy Maricela (2020)
The purpose of this research was to improve thc learning development of Logical-Mathematical Relations through intercultural leisure activities “I learn by playing” in students of First Year of Basic General Education at “Manuel Rodríguez Orozco” Educational Unit. The problem in the institution was gameless learning, which is why the students do not like mathematics. They consider it a difficult and boring subject; the misuse of electronic media has replaced that momento of fun, making it challenging to acquire communication and social skills, evidencing cases of discrimination against the Kichwa language. The research has a quantitative approach, the activities applied. the data obtained, and the analysis carried out within the contex. It was fieldwork, the hypothetical-deductive method was used. The information was collected through a checklist; experts and pedagogical professionals validate it. A diagnosis of the level of learning was carried out. It reflects that the students were at the beginning and in the process of knowledge; After lhe proposal´s application, the children achieved the skills assessed. Intercultural games were applied for both cognitive and motor development. Through these activities, the researcher sought that students like the mathematical field in a croos-cultural way. These activities were designed on the website ¨I learn by playing.” Finally, it is concluded that intercultural leisure activities improved the Logical-Mathematical Relations scope in the teaching-learning process.